Functional ceria-based nanocomposites for advanced low-temperature (300–600 °C) solid oxide fuel cell: A comprehensive review. (March 2020) - Raza, Rizwan; Zhu, Bin; Rafique, Asia; Naqvi, Muhammad Raza; Lund, Peter
Abstract: There is world tendency to develop SOFC to lower temperatures and two technical routes and approaches are going in parallel. One is to use thin film technology, focussing on reducing the electrolyte thickness on conventional electrolyte, e.g. YSZ (yttria-stabilized zirconia) and SDC (samaria-doped ceria) to reduce the cell resistance i.e. to lower the operational temperatures. Another technique is to develop new materials, e.g. functional nanocomposites. This paper presents a state-of-the-art of nanocomposite electrolytes-based advanced fuel cell technology, i.e. low-temperature (300–600 °C) ceria-based fuel cells, a new scenario for fuel cell R&D with an overview of important aspects and frontier subjects. A typical nanocomposite has a core–shell type structure in nano-scale, in which ceria forms a core and a salt, e.g. carbonate or another oxide develops a shell layer covering the core. The functionality of nanocomposites is determined by the interfaces between the constituent phases, which can lead to super or fast ions transport (H + and O 2− ) at interfaces. Ionic conductivities >0.1 S cm −1 already at ~300 °C have been reported. Five major characteristics of nanocomposites have been identified as important to their properties and applications in fuel cells: i) advanced materials design based on non-structure or interfacial properties/mechanisms; ii) dual or hybrid H + and O 2− conduction; iii) interfacial super-ionic conduction; iv) transition from non-functional to functional materials; v) use of interfacial and surface redox agents and reactions. In the fuel cell context, it is refer to these functional nano-composites as NANOCOFC (Nanocomposites for Advanced Fuel Cells) to distinguish them from the traditional SOFCs and to be oriented to a new fuel cell R&D strategy. Highlights: Review of advanced low temperature fuel cell with high performance. Significance of nanocomposite material with multi-functions. Role of superionic conduction and interface in fuel cell. Advanced nanocomposite materials and its theoretical aspects.